Avaliação do ajuste marginal de componentes protéticos estéticos sobre intermediário ceraone - Neves, José Bernardes das (2005)
The search for aesthetics in single implant restoration has increasingly prioritized the use of pure ceramics components in order to try and substitute the use of the metal-ceramic crowns. A number of techniques and materials have been developed with the purpose to overcome the difficulties in the attainment of prosthesis in pure ceramics or either, prostheses that present, beyond the aesthetic quality of conventional ceramics, resistance mechanics and adequate marginal adaptation. The success of the single prosthetic restoration, supported by osseointegrated implants and the health of the surrounding tissues, is closely related to the precision and the adaptation of the components and the stability of the interface / abutment / prostheses pillar. The Brãnemark system, in the 90 s presented, the CeraOne abutment as a solution for the single tooth losses that consist of modifications and adaptations of the screwed prosthesis for the cemented restoration. Ten gold cylinders (Group 1), ten coping of alumina oxide (Group 2) and ten of Procera scanned All Ceram (Group 3), adapted on a brass base of cylindrical form, measuring 4cm of length x 2,5cm of diameter, contend six faces numbered and uniforms, were used as test body. In the center, one perforation with 4mm of diameter x 10mm of depth was confectioned in which was fixed an implants of 10 x 3,75mm (Nobel Biocare). In the CeraOne a vertical and horizontal laser marks were drawn in each face of the hexagon as a reference. The fits had been evaluated before and after the face-hardenings with the elastomer, with and without vibration, constituting three groups of ten bodies of each test. A comparing microscope Mitutoyo (Japan) was used with increase of 150 times for the reading of the measures and with precision of 1µm. The results for the test of Fisher in level of 5% of probability demonstrate that the group most steady was of the gold cylinder, with coefficient of 29, 43% variation; the group most unstable was the group of Procera All Ceram scanned with coefficient of 106,50% variation. In accordance with the statistic analysis of the fit marginal of the aesthetic prostheses, it could be concluded that: a) the three studied conditions (gold cilinder, coping of alumina oxide premachined and coping of alumina scanned) have shown statistically similar results amongst them regarding the values of marginal fit; b) it did not have statistics significant difference in the reduction of the fit with the utilization of vibration, in the three studied experimental conditions.